Effect of duration of exposure on health complaints, systemic inflammatory responses, immunological markers, and pulmonary function tests among workers working at the vegetable market - Kalahasthi Ravibabu; Vinay Kumar Adepu; Jamalpur Ravi Prakash; Raju Nagaraju; Jakkam Surendar (Indian Journal of Allergy Asthma and Immunology, 2022)
BACKGROUND: The vegetable markets are a rich source of organic dust and bioaerosol exposure. The effect of duration of exposure on health complaints, systemic inflammatory responses (SIR), immunological markers, and pulmonary function tests (PFT) among loading and unloading workers at the vegetable market was not explored. OBJECTIVE: The current study was undertaken to assess the effect of duration of exposure on health complaints, SIR, immunological markers, and PFT among workers working at the vegetable market. MATERIALS AND METHODS: The study design is descriptive, 45 male participants with no smoking habit and having more than 3 years of experience were enrolled in the study. The study participants were categorized into low (n = 23) and high (n = 22) exposure groups based on the median duration of exposure, which is the multiplication of years of exposure and working hours per day. The demographic details, health complaints, SIR, immunological, and PFT parameters were investigated and compared between low and high exposure groups. RESULTS: Workers with a prolonged duration of exposure have reported a considerable increase in musculoskeletal disorders, eye irritation, and skin allergies. SIR such as serum albumin, high sensitivity C-reactive protein, lymphocytes, white blood cell count, and immunological markers (immunoglobulin E and immunoglobulin A) were considerably increased, and PFT were significantly decreased in the high exposure group as compared to the low-exposure group. CONCLUSIONS: Contemporary study revealed that high duration of exposure contributes to augmented health complaints, SIR, immunological markers, and reduced competence of PFT among loading and unloading workers at vegetable markets. Therefore, this study suggests workplace hygiene practices with the use of personal protective equipment might lower the health effects and inflammation markers.